Determination of online quenching efficiency for an automated cellular microfluidic metabolomic platform using mass spectrometry based ATP degradation analysis - Filla, Laura A.; Sanders, Katherine L.; Coulton, John B.; Filla, Robert T.; Edwards, James L. (Analytical and bioanalytical chemistry, 2019)
As microfluidic cell culture progresses, the need for robust and reproducible intracellular analyses grows. In particular, intracellular metabolites are subject to perturbation and degradation during the lysing process. The reliability of intracellular metabolomic analysis in microfluidic devices depends on the preservation of metabolite integrity during sample preparation and storage. Described here is a novel automated microfluidic system exhibiting the necessary rapid cellular lysis and quenching of enzymatic activity. Quenching efficiency was assessed using a novel ratiometric MALDI-MS-based assay of exogenous isotopic adenosine triphosphate (ATP) hydrolysis to isotopic adenosine diphosphate (ADP) as a marker of metabolite degradation. The lysis system of the microfluidic device was enhanced using a Peltier cooler to chill the lysate and quench aberrant enzymatic activity. Parameter optimization (flow rate, collection time, and temperature control) improved the endogenous and exogenous ADP/ATP ratios by 44.9% and 39.8% respectively consistent with traditional quenching techniques. The effects of chilling/quenching on metabolism were evaluated resulting in over 500 significant features compared to non-chilled from untargeted capillary LC-MS metabolomic analyses. These include increased levels of tryptophan, histidine, and pyruvate as well as decreased levels in UDP- N -acetylglucosamine. The results illustrate the need for both rapid lysis and quenching in microfluidic cell culture platforms. Graphical abstract